Implementasi Sistem Pemantauan Kondisi Ruangan Menggunakan Jaringan Sensor Nirkabel Berbasis Protokol RF24Network - Ahmat Choeri (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Wireless Sensor Network (WSN) is an infrastructure consisting of a number sensor nodes that are distributed in certain environments and coordinated using a wireless network. WSN can be implemented using the nRF24L0. One protocol that supports the nRF24L0 is the RF24 protocol. But for the implementation of monitoring the vast room conditions this protocol has the disadvantage of using a single-hop mechanism. So that for a large area range, multi-hop mechanism is needed. The RF24Network protocol is a designed to meet the needs of RF24-based multi-hop mechanisms, users simply build a header that contains the correct destination address and the network will forward it to the destination node. In accordance with the above problems, the authors implement sensor nodes using Arduino Nano as Microcontroller, nRF24L01 for communication and DHT11 to acquire sensor data. From the implementation results obtained network performance for monitoring the condition of the room with the level of accuracy of data transmission and delay as follows. Single-hop data transmission mechanism without barrier distance 3-12 meters 100% accuracy, 15 meters 70%, 18 meters 40%, 21 meters 0% with a total average delay of 145 ms, with a distance barrier of 3-9 meters 100% accuracy, 12 meters 60%, 15 meters 30%, 18 meters 0% with a total average delay 276 ms. Multi-hop mechanism of data transmission accuracy reaches 100% with average delay (1 hop without barrier 110 ms with a distance 24 meters, with barrier 270 ms with a distance 18 meters. 2 hops without barrier 270 ms with a distance 36 meters , with barrier 350 ms with a distance 27 meters, 3 hops without barrier 280 ms with a distance 48 meters, with a barrier 260 ms with a distance 36 meters).